The biology of the anchovy Engraulis capensis in the Benguela Current region - Melo, Y. C.(Yolanda Carolina) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.